Nesaeoduvalius (gen. n.) vailatii sp. n., from Euboia island (Eastern Greece) (Coleoptera: Carabidae, Trechinae) - Casale, Achille; Giachino, Pier Mauro (Fragmenta entomologica, 2016)
Nesaeoduvalius (new genus) vailatii Casale & Giachino, new species (Coleoptera: Carabidae: Trechini) is described and illustrated from the Euboia (Evvia) island (eastern Greece). The new taxon belongs to the Duvalius “isotopic” trechine lineage, but is markedly characterized by the peculiar combination of several morphological features in the general shape, chaetotaxy of head, serrate lateral margins of elytra, and features of male genitalia (both in median lobe of aedeagus and endophallus). Its putative position amongst the trechines of the Duvalius phyletic lineage is discussed. Data on the distribution and habitat of this new, insular and unexpected taxon are also provided.